2017
DOI: 10.1111/jsr.12561
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pulse oximetry and cerebral oxygenation in children with severe sleep apnea–hypopnea syndrome: a pilot study

Abstract: Near infrared spectroscopy (NIRS) has been used to assess the impact of obstructive sleep apnea-hypopnea syndrome (OSAHS) on cerebral oxygenation. However, the relationship between the variations in the cerebral tissue oxygen saturation (ΔTOI) and pulse oximetry (ΔSpO ) has not been assessed in children with OSAHS. Consecutive clinically stable children with severe OSAHS [apnea-hypopnea index (AHI) >15 events h ] diagnosed during a night-time polygraphy with simultaneous recording of cerebral oxygenation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…Previous studies have investigated changes in NIRS parameters associated with different types of apnea. Significant oscillations of cerebral hemodynamics with declined HbO 2 , tHb, and TOI/StO 2 accompanied by a synchronized increase in HHb were observed during the initiation of apneic episodes, and reverse changes of hemoglobin indices accompanied by inconsistent changes in tHb were obtained after the termination of apnea (71)(72)(73)(74)(75)(76)(77)(78)(79). An example of the changes of NIRS indices in response to apnea is shown in Figure 4.…”
Section: Cerebral Hemodynamics Under Different Sleep-disordered Breatmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have investigated changes in NIRS parameters associated with different types of apnea. Significant oscillations of cerebral hemodynamics with declined HbO 2 , tHb, and TOI/StO 2 accompanied by a synchronized increase in HHb were observed during the initiation of apneic episodes, and reverse changes of hemoglobin indices accompanied by inconsistent changes in tHb were obtained after the termination of apnea (71)(72)(73)(74)(75)(76)(77)(78)(79). An example of the changes of NIRS indices in response to apnea is shown in Figure 4.…”
Section: Cerebral Hemodynamics Under Different Sleep-disordered Breatmentioning
confidence: 98%
“…The occurrence of apneic episodes was accompanied by fluctuations in cerebral hemodynamics. The majority of studies have investigated the changes in cerebral tissue hemoglobin indices (HbO 2 , HHb, tHb) with and without CPAP or noninvasive ventilation (NIV) treatment in patients with OSA to evaluate the effect of treatment (72,77,78,89,97). Consistent reductions in the fluctuations of HbO 2 , HHb, and TOI were found in children and adults during CPAP.…”
Section: The Evaluation Of Treatment Efficacy Of Positive Airway Presmentioning
confidence: 99%
“…Pulse oksimetre kullanımı; yoğun bakım gerektiren, özellikle oksijenasyonu stabil olmayan ve sedatize edilmiş çocuklarda, hipokseminin ciddi sonuçlarının azaltılmasını, düzeltilmesini ve erken belirlenmesini sağlamaktadır. (16) Santral kateter yerleştirilmesi, bronkoskopi, endoskopi ve kardiyak kateterizasyon gibi invaziv işlemler, çocukta hipoksemi riskini arttırdığı için oksijen saturasyonu pulse oksimetre kullanılarak daha doğru olarak değerlendirilebilmektedir. (17) Pulse oksimetre, obstrüktif uyku apnesi şüphesi olan çocukların değerlendirilmesini de sağlamaktadır.…”
Section: Pulse Oksimetre Takibi Gerektiren Durumlarunclassified
“…Bu nedenle yapılan işlemin ağrı ve acı vermeyeceği çocuk ve ailesine anlatılmalı ve örnek olarak hemşire kendi üzerinde örnek bir ölçüm gerçekleştirerek çocuk ve ailenin rahatlamasını sağlamalıdır. (16) Probu yerleştirmeden önce probun yerleştirildiği bölgenin kuru ve temiz olması sağlanmalıdır. Prob çocuğun ayak ya da el parmağına yerleştirilecekse çocuğun tırnağında oje olup olmadığına bakılmalıdır.…”
Section: Hemşirelik Bakımıunclassified
“…Furthermore, adult studies have demonstrated decreased cerebral oxygenation in patients with OSA compared with controls (Hayakawa et al 1996;Valipour et al 2002;Schwarz et al 2018). There have been only three studies assessing cerebral oxygenation in children with SDB and although they identified that changes in brain oxygenation are seen in relation to obstructive events without changes in peripheral oxygenation, only small differences in cerebral oxygenation were found between children with SDB and non-snoring control children when averaged across the sleep stages (Khadra et al 2008;Olmo Arroyo et al 2017;Tamanyan et al 2018). It is possible that the repetitive bradycardia and tachycardia which occur during and following respiratory events, respectively, are accompanied by repetitive changes in cerebral oxygenation.…”
Section: Introductionmentioning
confidence: 99%